Bis{μ-N-[1-(2-oxidophenyl)ethylidene]benzo-hydrazido} bis[(dimethylsulfoxide)zinc(II)] - Ali, Hapipah Mohd; Yamin, B.M.; Yusof, M.S.M.; Kadir, Z. (International Union of Crystallography, 2003)
The title compound, [Zn2(C15H12N 2O2)2(C2H6OS) 2], is a centrosymmetric dimer via a Zn-O bridge of 2.0038 (13) Å, with a Zn⋯Zn separation of 3.1370 (13) Å. The geometry of the five-coordinate environment of the Zn atoms is close to trigonal bipyramidal. © 2003 International Union of Crystallography Printed in Great Britain - all rights reserved.